A Study on Corporate Demand from Business Management Graduates - Nandal, Dr. Naveen; Nandal, Nisha; Dr.Milind (The journal of contemporary issues in business and government, 2021)
This study was an attempt to understand the key reasons why management graduate students are failing in getting the better placements. From the last five years the placements of the management graduates has drastically reduced and some of the research studies has shown that the decline in the placements of the some of the tier two b-schools are just because of the reasons that they are not able to meet the requirement of the corporates so this study is an attempt to understand the various skills sets demanded by the industry and what are the keys skills that the students has to be trained in the colleges to make them corporate ready. This study was conducted with the help of the research questionnaire which helped in collecting the data from 697 students and 92 recruiters of the various companies who visits the business schools for the campus recruitment. The study was significant to understand the key skills demanded by the industy.